Pengaruh Modal Kerja terhadap Likuiditas Koperasi KUAT Subak Guama - REDANA, GEDE PUJA; SUAMBA, I KETUT; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018DO - 10.24843/JAA.2018.v07.i04.p07, 2018)
The Effects of Working Capital on the KUAT Cooperative Liquidity of Subak Guama KUAT Cooperative of Subak Guama is the manager of subak’s assets sourced from both macro and micro capitals as an effort to empower the members of Subak Guama in order to facilitate the farming services to achieve the common prosperity. The purpose of this study is to investigate the effect of working capital on the liquidity of KUAT Cooperative of Subak Guama during the period of 2008 to 2017 and to analyze the constraints in controlling the working capitals. Analyzer in this research was analysis of ratio of finance and doubled linear regression. The results showed that the effect of cash turnover, receivable turnover, and inventory turnover simultaneously have a significant influence on liquidity. Partial research results show that the turnover of receivables and inventory turnover have a significant influence on liquidity whereas cash turnover has no significant effect on liquidity. The result of the research on the constraint to control working capital is caused by the lack of awareness of the members in fulfilling the mandatory savings and there are still bad credits of 13% so that it requires the control of loans to members and non-members who apply for loans in KUAT Cooperative of Subak Guama.